Routes of Spread of Anthrax in Natural Ecosystems - V. S. Timofeev; I. V. Bakhteeva; G. M. Titareva; Yu. O. Goncharova; I. A. Dyatlov (Проблемы особо опасных инфекций, 2021)
Anthrax is a particularly dangerous zooanthroponosis caused by the Gram-positive spore-forming bacterium Bacillus anthracis. This disease mainly affects hoofed herbivores, including those used in agriculture, but can occur in other animals and in humans. That is why the majority of studies of this infection are focused on anthrax in humans and farm animals, as the most important issues from a practical point of view. At the same time, the issues of anthrax epidemiology in natural ecosystems are described in the literature in insufficient detail and often very fragmentary. This paper provides a review of the literature describing the main pathways, patterns and risks of the spread of various clinical forms of anthrax infection in nature, primarily among wild animals. Among other things, we cover some non-notable aspects of intestinal infection with anthrax which, for instance, explain the difference in sensitivity to infection in herbivorous and carnivorous mammals and even different sex and age groups within the same species.